1989
DOI: 10.1128/jvi.63.10.4422-4425.1989
|View full text |Cite
|
Sign up to set email alerts
|

Trans activation by the bovine papillomavirus E2 protein in Saccharomyces cerevisiae

Abstract: The papillomavirus E2 protein functions as an enhancer-binding factor to promote transcription in mammalian cells. We found that one copy of the E2 binding site acted as an E2 protein-dependent upstream activating sequence in Saccharomyces cerevisiae. Additional copies of the binding motif further augmented transcription. These results imply that the E2 protein functionally interacts with highly conserved transcriptional elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…from a promoter with two mutated E2 binding sites as the upstream element. It has been previously reported that amino-terminally truncated E2 proteins such as E2-R do not activate the E2 enhancer motif in rodent (Lambert et al, 1987;Haugen et al, 1988) and yeast cells (Morrissey et al, 1989). Since PV infection and pathologic effects are generally limited to epithelial cells (an exception is fibroma in some animals) we questioned whether E6 trans-activation function was operative in the lower eukaryote S. cerevisiae.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…from a promoter with two mutated E2 binding sites as the upstream element. It has been previously reported that amino-terminally truncated E2 proteins such as E2-R do not activate the E2 enhancer motif in rodent (Lambert et al, 1987;Haugen et al, 1988) and yeast cells (Morrissey et al, 1989). Since PV infection and pathologic effects are generally limited to epithelial cells (an exception is fibroma in some animals) we questioned whether E6 trans-activation function was operative in the lower eukaryote S. cerevisiae.…”
Section: Resultsmentioning
confidence: 95%
“…Since a BPV E6 responsive DNA element has not been identified, the E6 coding region was molecularly cloned onto the DNA binding domain of BPV E2, creating E6-E2-R ( Figure 1). This E2-R region lacked the E2 activation domain and is unable to induce E2 elements in mammalian cells and yeast (Lambert et al, 1989;Morrissey et al, 1989). The fusion gene was constructed to preserve the BPV E6 protein, with the only alteration of E6 limited to a conservative change of lysine to arginine two amino acids prior to its terminal proline.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations